Informal sells better - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Elsewhere in Cameroon, a new multi-storied market was built in the 1970s on the site of the old central market. It was a futuristic building and its circular form made it an architectural curiosity for quite some time. Traders fought to get stands...